Formulation and test activities of hair tonic with a combination of the aqueous extracts of aloe vera ( Aloe vera L.) and licorice (Glycyrrhiza glabra L.) - Sulistiorini Indriaty; Teti Indrawati; Shelly Taurhesia (Pharmaciana, 2018)
Aloe vera contains lignin, folic acid, vitamin A, and 20 types of amino acids, while Glycyrrhiza glabra L. contains glycyrrhizin, steroids, and beta-glycyrrhetinic acid that benefit for hair health. This research aimed to produce hair tonic with the best activity from the combination of aloe vera and licorice extract. The phytochemicals in the aqueous extract of licorice and Aloe vera were screened. The hair tonic was then prepared with 3 formulas using 7.5% Aloe vera extract and 2.5% licorice extract, as well as 96% ethanol with varying percentages, namely 5, 10, and 15%. Afterward, the formulas were tested for their activity as hair fertilizer on 4 white male rabbits for 28 days. The evaluation of hair tonic preparation included organoleptic observation, pH, specific weight, viscosity, and hedonic tests. It measured hair growth rate, the acceleration of hair growth, and hair weight. The results showed that hair tonic containing a mixture of 7.5% of Aloe vera extract, 2.5% of licorice extract, and 96% ethanol with different percentages (i.e., 5, 10, and 15%) created a good hair fertilizer. Hair tonic prepared with 15% of 96% ethanol exhibited an optimum activity. It was characterized by brown color, distinctive odor, homogeneity, a specific weight of 1.0577 g/mL, a viscosity of 2.8479 cP to distilled water, and pH 5.5. Its effectiveness as hair fertilizer was evidenced by a hair growth rate of 2.6617 cm in 28 days, a hair growth acceleration of 0.1635 cm/day, and a hair weight of 0.1854 gram in 28 days.